Rare Association between Giant Right Ventricular Myxoma and Right Coronary Artery Tumour Blush with Complicating Pulmonary Tumour Embolism - Robin Yeong Hong Goh; Shreeja Mehrotra; Stefan Buchholz; Deepak Mehrotra; Allison Morton (Case Reports in Cardiology)
Cardiac myxoma is a benign primary cardiac tumour which can present with nonspecific symptoms of right heart failure, syncope, exertional dyspnea, and pulmonary embolism. We describe a case of a right ventricular myxoma complicated with bilateral pulmonary embolism, with an incidental right coronary artery fistula but otherwise normal coronary anatomy on coronary angiogram. This case report emphasizes the importance of performing a transesophageal echo in the setting of pulmonary embolism to search for the origin of thrombus/tumour, and performing a comprehensive assessment is also necessary to rule out coronary artery disease, coronary artery fistula that may also represent a tumour blush.